Resin infiltration: case series - Waleed Asiri (Amaltea Medical Publishing House, 2023)
Background. Hypomineralization of the incisors and first molars (MIH) is distinguished by a systemic enamel maturation condition that influences minimum single permanent first molar and is frequently linked to incisor enamel deficiencies. The estimated incidence of MIH is 12.9% (11.7-14.3%). To our knowledge, no case series has been presented in the literature that discusses the resin infiltration technique for aesthetic management of MIH of enamel. Aim. This case series discusses four cases where MIH has been effectively managed by the resin infiltration technique. Case presentation. The diagnosis of MIH was made after careful evaluation of the defects during clinical follow-up, considering the patient's previous medical history, and making a diagnostic evaluation with other enamel abnormalities. The same dental professional applied resin infiltration (Icon, DMG America; Englewood, USA), and there were regular follow-ups after the procedure. After the resin infiltration procedure, the patients were asked about their comfort throughout the procedure, satisfaction with the results, and whether they would suggest this intervention to others. Results. At follow-up, patients remarked that they felt at ease throughout the procedure, expressed satisfaction with the results, and said they would recommend this course of treatment to others. Conclusion. High patient contentment with resin infiltration treatment was reported in all four cases, which successfully obscured MIH on teeth of the maxillary anterior region.